Skeletal pathologies track body plan evolution in ichthyosaurs - Pardo Perez, Judith Mariana; Kear, Benjamin P.; Maxwell, Erin E. (My University, 2020)
Changing predator-prey interactions during the Mesozoic Marine Revolution (MMR) profoundly altered the trajectory of marine tetrapod evolution. Here, we assess potential signatures of this landmark transition through the fossil record of skeletal pathologies in ichthyosaurs - iconic marine reptiles that developed increasingly 'fish-like' body plans over time. We surveyed a stratigraphically constrained sample of 200 Middle Triassic ichthyosaur specimens and compared the type, distribution and prevalence of pathologies with an approximately equivalent assemblage of Early Jurassic age. Overall, skeletal pathologies were equally prevalent in these groups, and most often manifested in species >4m long. However, pathological bones were found to be concentrated in the hind limbs and tail of Triassic ichthyosaurs, whereas the jaws, forelimbs, and ribcage were preferentially affected in Jurassic taxa. We posit that the occurrence of ankylosed zygapophyses in the caudal peak of Triassic ichthyosaurs could represent a functional by-product of their primitive 'eel-like' swimming. Conversely, increased instances of broken ribs in Jurassic ichthyosaurs may infer ramming or tail strike behaviours that characterise morphologically 'fish-like' marine tetrapods, such as modern toothed whales. Different categories of skeletal pathologies thus evidently reflect structural modifications in the ichthyosaur body plan, and indirectly coincide with ecological turnover during the MMR.
Keywords: Body plan; Tetrapod (structure); Elasmobranchii